Indonesian consumers’ emotional and psychological factors in the nexus of fear of missing out (FOMO) - I Made Sindhu Yoga; Ni Putu Intan Sistadyani; Raja Sharah Fatricia; Dhiani Rani Yulianti; Ida Nyoman Basmantra (BISMA (Bisnis dan Manajemen), 2022)
This research examines the effect of emotional and psychological factors and their implications for fear of missing out (FOMO) on the online music platform. The object of this study is Spotify. The population in this study was respondents in Indonesia. The purposive sampling technique was used, where the sample criteria used consisted of Spotify users who have seen the Spotify Wrapped campaign at least once on social media. The SEM-AMOS is use to analyzed questionnaire data of 150 respondents. It was found that the varying psychological needs relatedness and unfulfilled psychological needs for self will positively affect FOMO. The result also shows that anticipated elation and anticipated envy from others have a positive effect on FOMO. It was also found that comforting rationalizations negatively influence FOMO and FOMO positively and significantly affect purchase intention. This study finds that comforting rationalization explains concerns about alternatives and offers behavioural mitigation that assist individuals to make their choices and reduce their FOMO.